2020
DOI: 10.3390/s20061558
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of magnetic properties and GMI effect of Thin Co-rich Microwires for GMI Microsensors

Abstract: Magnetic microwires can present excellent soft magnetic properties and a giant magnetoimpedance effect. In this paper, we present our last results on the effect of postprocessing allowing optimization of the magnetoimpedance effect in Co-rich microwires suitable for magnetic microsensor applications. Giant magnetoimpedance effect improvement was achieved either by annealing or stress-annealing. Annealed Co-rich presents rectangular hysteresis loops. However, an improvement in magnetoimpedance ratio is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 66 publications
3
63
0
Order By: Relevance
“…Thus, in certain stress-annealing conditions, Co 68.7 Fe 4 Ni 1 B 13 Si 11 Mo 2.3 microwires with rectangular hysteresis loops and extremely low coercivity of about 1A/m can be obtained (see Figure 21) [102]. In the case of Co-based microwires higher annealing temperature, time or stresses are required to prevent magnetic hardening associated with relaxation of internal stresses related to glass-coating [42,43,101]. As can be observed in Figures 19 and 20, for extended range of Tann, tann or σm, stressannealed Co-rich microwires present rectangular hysteresis loops.…”
Section: Effect Of Induced Magnetic Anisotropy On Hysteretic Magneticmentioning
confidence: 99%
“…Thus, in certain stress-annealing conditions, Co 68.7 Fe 4 Ni 1 B 13 Si 11 Mo 2.3 microwires with rectangular hysteresis loops and extremely low coercivity of about 1A/m can be obtained (see Figure 21) [102]. In the case of Co-based microwires higher annealing temperature, time or stresses are required to prevent magnetic hardening associated with relaxation of internal stresses related to glass-coating [42,43,101]. As can be observed in Figures 19 and 20, for extended range of Tann, tann or σm, stressannealed Co-rich microwires present rectangular hysteresis loops.…”
Section: Effect Of Induced Magnetic Anisotropy On Hysteretic Magneticmentioning
confidence: 99%
“…However, it has been recently noticed that conventional annealing produces a considerable magnetic hardening in different Co-rich microwires with vanishing λ s -values [32,33]. Such magnetic hardening is a detriment to the GMI performance [27,32,33]. Nevertheless, we have recently observed that stress-annealing can be successfully employed to induce a transverse anisotropy and hence improve the GMI effect of magnetic microwires [27,32,33].…”
Section: Introductionmentioning
confidence: 96%
“…In this regard, at a fixed composition and geometry (metallic nucleus diameter and glass-coating thickness) the magnetic anisotropy can be fine-tuned either by the internal stresses relaxation (usually by conventional annealing) or by inducing magnetic anisotropy [27,32]. However, it has been recently noticed that conventional annealing produces a considerable magnetic hardening in different Co-rich microwires with vanishing λ s -values [32,33]. Such magnetic hardening is a detriment to the GMI performance [27,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Co-based microwires higher annealing temperature, time or stresses are required to prevent magnetic hardening associated to relaxation of internal stresses related to glass-coating [42,43,101]. As can be observed in Figures 19 and 20, for extended range of Tann, tann or σm, stress-annealed Co-rich microwires present rectangular hysteresis loops.…”
Section: Effect Of Induced Magnetic Anisotropy On Hysteretic Magneticmentioning
confidence: 96%